Analysis of the influence of service quality on customer satisfaction using the customer satisfaction index and servqual methods: a case study of PT Charoen Pokphand Indonesia - Syarifuddin, Rizal; Asrul, Muhammad (Operations Excellence: Journal of Applied Industrial Engineering, 2025)
This study analyzes the influence of service quality on customer satisfaction at PT Charoen Pokphand Indonesia Tbk., Makassar Branch, using the Customer Satisfaction Index (CSI) and SERVQUAL methods. A questionnaire was employed to measure satisfaction levels, while SERVQUAL assessed five service dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Results show a CSI score of 82.10%, placing customer satisfaction in the “Good” category. The responsiveness dimension had the largest gap, indicating a need to enhance service speed and responsiveness. Meanwhile, the tangible dimension had the smallest gap, suggesting potential improvements in physical aspects like cleanliness and facilities. Security concerns also emerged as a notable gap. Based on the gap analysis, improvements in tangible aspects and security systems are recommended to enhance customer loyalty and competitiveness.